PERAN WORD OF MOUTH MEMEDIASI PENGARUH KEPUASAN TERHADAP LOYALITAS KONSUMEN PADA GREEN PRODUCT MEREK ORIFLAME DI KOTA DENPASAR - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Made Kansa Dewi Putri (UNHI Press, 2018)
Increased human awareness of the importance of preserving natural resources has made many producers of various types of products begin to switch to using materials that do not damage the environment or known as green products. This change in the concept of marketing based on the environment requires the right marketing strategy to create customer satisfaction and loyalty. Retained customers will be happy to express positive things and provide recommendations about products to others (Word of Mouth). This research was conducted on consumers in the city of Denpasar by using data from the number of Oriflame consultants as many as 100 people. Data were analyzed by path analysis techniques, where the validity and reliability tests were carried out in the initial stages of testing. The results of the analysis show that satisfaction and word of mouth have a significant effect on consumer loyalty on the Oriflame brand green product. Word of Mouth also plays a role in mediating the effect of satisfaction on consumer loyalty on the Oriflame brand green product. For this reason, to encourage positive word of mouth from consumers, the combination of product quality and good service quality will encourage customer satisfaction which ultimately leads to an increase in customer loyalty.